Approximation Methods for Common Fixed Points of Mean Nonexpansive Mapping in Banach Spaces. (15th January 2008) - Gu, Zhaohui; Li, Yongjin
Abstract : LetX be a uniformly convex Banach space, and letS, T be a pair of mean nonexpansive mappings. In this paper, it is proved that the sequence of Ishikawa iterations associated withS andT converges to the common fixed point ofS andT .